Beyond absorptive capacity in open innovation process: the relationships between openness, capacities and firm performance. Issue 9 (20th October 2016) - Ahn, Joon Mo; Ju, Yonghan; Moon, Tae Hee; Minshall, Tim; Probert, David; Sohn, So Young; Mortara, Letizia
ABSTRACT: The literature has shown that open innovation (OI) can be a winning strategy in improving firm performance. However, in order to adopt and implement it, managers need to resolve practical problems, such as understanding the role played by OI capacities and openness on firm performance. In response to these needs, this study aims to investigate the hierarchical relationships between openness, OI capacities and performance using a structural equation model approach. This paper also attempts to compare the levels of openness between firms in different industries to discover similarities and differences in OI phenomena. The analysis of data obtained from a survey of Korean firms shows significant interrelations between openness, OI capacities and firm performance. Our results go further in developing understanding of the building blocks on which successful OI is built and particularly suggest that desorptive capacity which underpins the out-bound OI process, is in turn strongly supported by knowledge management capacity. It is hoped that the results of this study can enrich our understanding of the OI mechanism and provide managerial and policy implications.